Brain functional connectivity patterns in focal cortical dysplasia related epilepsy. (April 2021) - Liu, Wenyu; Lin, Mintao; Yue, Qiang; Gong, Qiyong; Zhou, Dong; Wu, Xintong
Highlights: Connections between brain networks in FCD group based on ICA. Significantly higher FC between frontal and temporal regions was shown in FCD group. Lower FC between cerebellum and frontal regions was also shown by seed-based FC. The normalized characteristic path length was significantly higher in FCD group. Abstract: Objective: Focal cortical dysplasia (FCD) appears to be strongly associated with intractable epilepsy. Although patients with FCD are candidates for epilepsy surgery, gray matter structural abnormalities can extend beyond the primary lesion, which makes surgery less effective. The objective of this study was to evaluate functional connectivity patterns in epilepsy associated with FCD to explore the underlying pathological mechanism of this disorder. Methods: A total of 34 patients (14 men) with FCD and epilepsy [mean age ± standard deviation (SD), 24.5 ± 9.8 years; range, 8–47 years] and 34 age-matched healthy controls (14 men, 24.6 ± 9.7 years) underwent functional magnetic resonance imaging. Independent component analysis (ICA), seed-based functional connectivity, and graph theory were applied to analyze functional connectivity patterns in the brain. Results: Patients showed more connections among dorsal attention network, anterior default mode network, and sensorimotor brain networks than healthy controls based on ICA. Analysis of connectivity between regions of interest (ROIs) showed greater functional connectivity in patients between frontal and temporal regions, but lower connectivity between the cerebellum and frontal regions. The normalized characteristic path length was significantly higher in group of patients, but the two groups showed no significant differences in global or regional efficiency, clustering coefficient or characteristic path length. Conclusions: Analysis of ICA-derived and ROI-based functional connectivity suggests that disrupted interactions and dysconnectivity in large-scale neural networks and frontotemporal-cerebellar regions may contribute to underlying pathological mechanisms in FCD-related epilepsy.